Five-Finger Hypnosis Lowers Anxiety in Elderly Hypertensive Patients - Indra Ruswadi; Kayubi; Nafisah Itsna Hasni (PROFESSIONAL HEALTH JOURNAL, 2025)
One of the health problems that can cause anxiety is hypertension and the psychological aspects that accompany it. Anxiety is a feeling of worry as if something bad is going to happen and a feeling of discomfort as if there is a threat accompanied by physical symptoms such as heart palpitations, cold sweats, and shaking hands. One alternative relaxation for hypertensive patients is five-finger hypnosis, which aims to program oneself, relieve anxiety, and reduce the increase in heart rate, respiration, and blood pressure. The purpose of the study was to determine the effect of complementary therapy with the five-finger hypnosis method on the reduction of anxiety in elderly hypertensive patients (Elderly) at the Sliyeg Health Center, Indramayu Regency. Research method: This research is a type of pre-experiment with a one-group Pre-test Post test design. The population of this study is all elderly hypertension patients who use health services at the Sliyeg Health Center, Indramayu Regency, as many as 263 people, and the sample used is accidental sampling, as many as 32 respondents. The data collection instrument in this study is the Hamilton Anxiety Rating Scale (HARS) questionnaire, which is standard and according to the standard operating procedure of 5-finger hypnosis. The data analysis techniques used are univariate and bivariate analysis using the Wilcoxon sign rank test because the data of nominal free variables and ordinal-bound variable data are ordinal. Results: Before being given 5-finger hypnosis therapy, the majority of respondents were at a severe anxiety level of 28 respondents (87.5%); after being given 5-finger hypnosis therapy, the majority of respondents were at a mild anxiety level of 20 respondents (62.5%), and the results of the paired sample t-test statistical test obtained a p-value of 0.000. Conclusion: There was a very significant or meaningful change in anxiety level before and after being given five-finger hypnosis (p-value < α 0.05). Suggestion: elderly hypertension patients should be given complementary therapy with the 5-finger hypnosis method to complement conventional treatment.